Are You Sleeping? Dyadic Associations of Support, Stress, and Worries Regarding Adult Children on Sleep. (24th January 2017) - Seidel, Amber J; Yorgason, Jeremy B; Polenick, Courtney A; Zarit, Steven H; Fingerman, Karen L
Abstract: Purpose of the study: Sleep is a key factor in maintaining positive health and well-being throughout life. Although the negative outcomes of sleep problems are becoming better understood, less is known about how intergenerational relationships might affect sleep. Thus, this investigation examines the dyadic associations of support for, stress over, and worrying about adult children on sleep quality for husbands and wives. Design and Methods: The sample included 186 heterosexual married couples drawn from the Family Exchanges Study. To account for nonindependence in the dyadic data and explore questions of mutual influence, we used actor–partner interdependence models. Results: Husbands' and wives' reports of supporting their adult child and husbands' worry were associated with husbands' sleep quality. Conversely, wives' stress about supporting their adult child was associated with wives' sleep quality. Findings suggest that relationships with adult children have different associations for sleep quality among middle-aged husbands and wives. Implications: Our findings have implications for health-related research with couples and families and for providers who work with individuals struggling with sleep problems. Assisting aging parents to be aware of and manage ways that stress, support, and concern for adult children relate to their sleep may benefit them in multifaceted ways.